EFFECTIVENESS OF SOCIO-SCIENTIFIC ISSUE-BASED E-MODULES IN FORMING ECOSYSTEM LITERACY AND SOCIAL AWARENESS OF ELEMENTARY SCHOOL STUDENTS - Erlina; Sumanti; Rambang Muharramsyah (RADJA PUBLIKA, 2026)
Scientific Issues for the Integrated Science and Social Studies (IPAS) subject, specifically on the ecosystem topic for fifth-grade elementary school students. The main objectives include: (1) analyzing the development procedure, (2) evaluating the validity level, (3) measuring practicality, and (4) testing the effectiveness of the e-module in improving students' learning outcomes and critical thinking skills. The research methodology employed a Research and Development (R&D) approach using the Plomp model, consisting of five phases: preliminary investigation, design, realization, evaluation-revision, and implementation. The trial subjects comprised 25 fifth-grade students from SD Negeri 2 Dewantara. Data were collected through expert validation (7 multidisciplinary validators), practitioner observation, student response questionnaires, as well as pre-test and post-test assessments analyzed using Shapiro-Wilk normality tests and N-Gain calculations. The results indicate that the e-module is highly valid (average score 4.62–4.81), highly practical (observation average 4.63; practicality percentage 83.64%), and highly effective, student learning mastery significantly increased from 28% to 88%, with 36% of students achieving “high” improvement category based on N-Gain. Students' responses were overwhelmingly positive, with 100% expressing enjoyment and 88% finding the material easy to understand. In conclusion, the SSI-based e-module proves to be an innovative pedagogical solution that bridges scientific theory with real-world social issues, enhances learning motivation, strengthens science literacy and critical thinking, and is therefore suitable for adoption and replication in other elementary schools.